(untitled) (Journal of Pharmaceutical Negative Results, 2023)
The goal of the current investigation was to assess the preclinical effectiveness of doxorubicin (DOX)induced cardiotoxicity and methanolic extract of Eclipta Alba (MEEA). Except for the control group, animals were separated into five groups at random and given either a vehicle (15 mg/kg, i.p.) or DOX (15 mg/kg, i.p.) or MEEA (200 and 400 mg/kg, p.o.) or conventional Digoxin for 14 days. On the 13th and 14th days of treatment, DOX was administered. DOXimpaired rats had a substantial (p0.05) rise in blood cardiac indicators (creatine kinase, lactate dehydrogenase, and cardiac troponinI), lipid peroxidation, and protein carbonyl content, as well as a decrease in the levels of antioxidants (SOD, CAT, Gpx, and GSH) in the heart tissue. MEEA (200 and 400mg/kg, p.o.) treatment returned the abnormal biochemical level to normal. As a result, the study's findings indicate that MEEA demonstratedPotential cardioprotective efficacy in DOXinduced heart injury, mediated by its membrane stabilising and antioxidant impact